Model zachowań konsumenckich na rynku usług turystycznych - Jedlińska, Maja (Consumers' behaviour model in the tourism market, 2005)
Success in the tourism market depends on prompt and correct recognition of clients’ needs and adjusting its offer to wishes of potential tourists. The knowledge related to consumers’ behaviour and their decision making processes becomes especially valuable. While conducting this type of research, economics has to cooperate with social psychology, sociology, philosophy and even biology. Universal model of consumers’ behaviour, which emphasizes both internal and external conditions, may be adopted for the needs of knowledge on tourism by introducing some specific problems which are characteristic for tourism movement. Therefore issues of lifestyle, decision taking rules, consumer’s involvement, rationale and freedom of choice are of such great importance.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2005; nr 1095, s. 193-208